2002
DOI: 10.1093/jae/11.2.169
|View full text |Cite
|
Sign up to set email alerts
|

How Low Can You Go? Combining Census and Survey Data for Mapping Poverty in South Africa

Abstract: Poverty maps, spatial descriptions of the distribution of poverty in any given country, are most useful to policy-makers and researchers when they are finely disaggregated, i.e. when they represent small geographic units, such as cities, towns, or villages. Unfortunately, almost all household surveys are too small to be representative at such levels of disaggregation, and most census data do not contain the required information to calculate poverty. The 1996 South African census is an exception, in that it doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 9 publications
0
52
0
Order By: Relevance
“…Simelton et al [14] observed that small droughts might have relatively large effects on maize yields in the face of inadequate adaptive capacity and vice versa because high adaptive capacity lowers vulnerability. A variety of socio-economic proxies have been suggested for use in indicator-based approaches for vulnerability assessment, including: level of education and poverty, availability of safety nets and transportation systems [68][69][70][71][72][73][74].…”
Section: Adaptive Capacity Indexmentioning
confidence: 99%
“…Simelton et al [14] observed that small droughts might have relatively large effects on maize yields in the face of inadequate adaptive capacity and vice versa because high adaptive capacity lowers vulnerability. A variety of socio-economic proxies have been suggested for use in indicator-based approaches for vulnerability assessment, including: level of education and poverty, availability of safety nets and transportation systems [68][69][70][71][72][73][74].…”
Section: Adaptive Capacity Indexmentioning
confidence: 99%
“…The basic idea is to impute income to households in the Population Census (and Population Counts), using a model that predicts income from a household survey. Empirical evidence based on this method has proven to be precise when applied to data from nations like Ecuador, South Africa, Brazil, Panama, Madagascar and Nicaragua (see Elbers et al 2003, Alderman et al 2002, and Elbers et al 2001. In addition, the small-area estimation methodology has key advantages as it benefits from the strengths of both household surveys and census and avoids their weaknesses.…”
mentioning
confidence: 99%
“…I begin by focusing on the one probit model for equation (1) and the eight separate probit models using equation (2). These results are reported in Table 8.…”
Section: Univariate Estimation Resultsmentioning
confidence: 99%
“…I estimated a probit model using the NCS-R data for whether one has any mental health problem using the speci…cation in equation (1). Based on the results in Tables 8 and 10, it seems to be important to allow for age to a¤ect prevalence ‡exibly.…”
Section: Results Using Ncs-rmentioning
confidence: 99%
See 1 more Smart Citation